The Impact of China's Economic Growth on Crude Oil Price: Evidence from Structural VAR - Hamendi, Ahmed Tarik; Law, Siong Hook (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2023)
This paper examines the impact of Chinese economic growth on the real price of crude oil based on monthly time series data from 1992:01 to 2017:06 using structural vector auto-regression (SVAR). The variables of the SVAR model are global crude oil production, index of global economic activity, China’s real GDP and real price of crude oil. Due to a break in the real price of oil series during the 2008 global financial crisis, the data is divided into two intervals. The results for the period prior to the 2008 crisis show that global demand shocks had a significant impact, while shocks from Chinese economic activity and global oil supply were insignificant. However, the results for the post 2008 period demonstrate that demand shocks of the Chinese economy have a significant but delayed impact, while global supply shocks have an immediate impact. The findings indicate a new regime after the 2008 crisis with a resurgence of a supply driven crude oil market structure that is influenced by Chinese economic performance.